Relationship between Preventive Behavioral Factors and Malaria Incidence in Endemic Areas of Lahat Regency in 2021 - Debby Andhika Putri; Hamzah Hasyim; Hilda Zulkifli; Ahmad Ghiffari; Chairil Anwar (HM Publisher, 2021)
Background: Malaria is still one of the main infectious diseases of concern in the world. Lahat Regency is a moderate malaria-endemic area in South Sumatra, where there are still several villages with an API value above 1 and indigenous cases, although the average API value in all health facilities is below 1. Methods: Quantitative research with a case-control design was employed. The sampling technique used stratified random sampling with year strata, namely 2018, 2019 and 2020 with 50 case respondents and 100 control respondents. The total number of samples collected was 150. Case respondents were people who suffered from malaria and are recorded in the Malaria Surveillance Information System in the working area of the community health center, which has a village with an API value of 1 and the presence of indigenous cases. Control respondents were the closest neighbours of cases with the same age characteristics as the case. This study aimed to identify and analyse risk factors for preventive behaviour related to malaria incidence in the endemic area of the Lahat Regency. Results: : Bivariate analysis revealed that the habit of using insect repellent was connected with the incidence of malaria in the endemic region of Lahat Regency, with a p-value of 0.042 and an odds ratio of 2.160 in the endemic area. The results of multivariate analysis showed that the most dominant risk factor was the habit of using mosquito repellent. Conclusions: The habit of using mosquito repellent is a risk factor for malaria incidence in endemic areas of the Lahat Regency. It is necessary to increase individual self-prevention behaviour and counselling activities regarding preventive behaviour by local health service facilities.